Implementasi Problem-Based Learning dalam Pembelajaran Kewirausahaan - Ali Muhson (Jurnal Ekonomi dan Pendidikan, 2005)
The aims of this research is to find out the effect of Problem-Based Learning model on increasing of students learning interest, students active role in the learning process, student self study activity as well as students knowledge and understanding of learning material. This research employs participatory action research, while the object is students of Economics Study Program enrolling entrepreneurship course academic year of 2004/2005. Based on the result of this research is drawn some conclusion as follow: 1) Problem-based learning model is able to raise attention and students active role in the learning process. students active role in the learning process, 2) this model is able to stimulate students learning interest and student self study activity 3), last but not least, the model is proven able to improve students knowledge and understanding of learning material.